Language in Britain and Ireland - Fox, Susan 1956- (Cambridge University Press, 2024)
Britain and Ireland are home to a rich array of spoken and signed languages and dialects. Language is ever evolving, in its diversity, and in the number and the backgrounds of its speakers, and so, too, are the tools and methods used for researching language. Now in its third edition, this book brings together a team of experts to provide cutting-edge linguistic and sociolinguistic information about all the major varieties of language used across Britain and Ireland today. Fully updated, this edition covers topics including the history of English, the relationship between standard and nonstandard Englishes, multilingualism in Britain and Ireland, and the educational and policy planning implications of this linguistic diversity. Chapters are also dedicated to specific language varieties, including comprehensive descriptions of the Celtic languages, nonstandard regional varieties, sign languages, and urban contact varieties. It is essential reading for academic researchers and students of sociolinguistics and education